2021
DOI: 10.3390/molecules26061792
|View full text |Cite
|
Sign up to set email alerts
|

PET Diagnostic Molecules Utilizing Multimeric Cyclic RGD Peptide Analogs for Imaging Integrin αvβ3 Receptors

Abstract: Multimeric ligands consisting of multiple pharmacophores connected to a single backbone have been widely investigated for diagnostic and therapeutic applications. In this review, we summarize recent developments regarding multimeric radioligands targeting integrin αvβ3 receptors on cancer cells for molecular imaging and diagnostic applications using positron emission tomography (PET). Integrin αvβ3 receptors are glycoproteins expressed on the cell surface, which have a significant role in tumor angiogenesis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 83 publications
0
28
0
1
Order By: Relevance
“…This conceptual change was consequently transferred to clinical investigations. Radiolabeled 'RGD-peptides' were frequently applied for tumor imaging, e.g., as a possible alternative to [ 18 F]FDG, quietly disregarding the question whether a tracer uptake might actually be related to angiogenesis or not [ 2 , 7 ]. It, however, seems to consolidate that the average αvβ3-integrin expression density on tumor cells and -endothelium is simply not sufficient to guarantee a clinical impact comparable to somatostatin receptor (SSTR)-, PSMA-, or fibroblast activating protein (FAP) targeted radiopharmaceuticals.…”
Section: αVβ3-integrin Targeting Radiopharmaceuticals—a Critical Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…This conceptual change was consequently transferred to clinical investigations. Radiolabeled 'RGD-peptides' were frequently applied for tumor imaging, e.g., as a possible alternative to [ 18 F]FDG, quietly disregarding the question whether a tracer uptake might actually be related to angiogenesis or not [ 2 , 7 ]. It, however, seems to consolidate that the average αvβ3-integrin expression density on tumor cells and -endothelium is simply not sufficient to guarantee a clinical impact comparable to somatostatin receptor (SSTR)-, PSMA-, or fibroblast activating protein (FAP) targeted radiopharmaceuticals.…”
Section: αVβ3-integrin Targeting Radiopharmaceuticals—a Critical Analysismentioning
confidence: 99%
“…In view of the popularity of cyclic pentapeptides of the cyclo[RGDxK] (x = y, f) type, it is hard to imagine that a greater variety of conjugates has been generated for any other small-molecule targeting motif. The same might apply to multimers thereof [ 2 ]. The impact of multiplicity has been evaluated for c[RGDxK]'s in several systematic studies, which invariantly showed that a higher degree of multiplicity increased the affinity of the constructs [ 78 85 ] and frequently resulted in improved in vivo targeting properties, i.e., higher target-specific uptake [ 86 , 87 ].…”
Section: Multimers Of Integrin Ligandsmentioning
confidence: 99%
See 3 more Smart Citations